INVESTIGATING THE EFFECTS OF PHYSICAL ACTIVITY LEVELS, DAIRY PRODUCTS AND CALCIUM INTAKES ON RISK FACTORS OF OSTEOPOROSIS PREVENTION IN FEMALE STUDENTS OF ISLAMIC AZAD UNIVERSITY OF DAMAVAND, IRAN - Marya, Rehmani Ghobadi; Rastegar, Hoseini (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Aim: Osteoporosis is a serious metabolic bone disorder that often results in hip fracture and usually asymptomatic in its initial stages. Since the majority of bone formation occurs during childhood and adolescence, it is important to begin primary prevention at an early age, although the optimal way for instilling this preventive behavior in youth has not yet been defined. The purpose of this study was to investigating the effects of physical activity levels, dairy products and calcium intakes on risk factors of osteoporosis prevention in female students of Islamic Azad university of Damavand in Iran. Methods: This cross sectional study was conducted on 280 healthy female university students aged between 18 to 24 years old who were selected randomly from the university students of Islamic Azad university of Damavand, Iran. Subjects completed an informed consent form, health history questionnaire; food questionnaire was used to assess the entire dietary component intakes and physical activity questionnaire (Baecke). Result: The result shows that Increase in physical activity and diary product consumption, the calcium intake with a decrease in BMI, and increase in BMD. Also results shows that there were significant negative correlations between the physical activity levels, diary product consumption, the calcium intake and risk factors of osteoporosis. Conclusions: Increased physical activity and diary product consumption, the calcium intake is associated with an increase in BMD and a concomitant decrease in BMI. These findings suggest that population-level interventions to increase physical activity and diary product consumption, the calcium intake would favorably impact bone and other health outcomes. Thus, dietary pattern coupled with higher education levels and greater physical activity favored bone health and osteoporosis prevention in middle school females.